A single surgeon's experience with transanal endoscopic microsurgery over 20 years with 153 early cancer cases. Issue 1 (January 2014) - Kanehira, Eiji; Tanida, Takashi; Kamei, Aya; Nakagi, Masafumi; Hideshima, Amane
Abstract Background: The first author performed transanal endoscopic surgery (TEM) in 302 patients in Japan for the last 20 years, 153 of which were early rectal cancer cases. The short- and long-term outcomes of the early rectal cancer cases are herein reported. Material and methods: The original technique of TEM developed by Gerhard Buess was performed in all cases. The hospital records were reviewed to assess the clinical outcomes. A questionnaire was sent to the patients to analyze the long-term outcomes. Results: One-hundred and fifty-three early cancer cases included 115 T0 and 38 T1 lesions. Full-thickness resection was performed in 36 patients, while 117 underwent submucosal dissection. Conversion to laparoscopic low anterior resection occurred in one case. Mortality was nil. Major operative complication was noted in only one patient, who developed stenosis. Seven patients underwent immediate salvage surgery. Six patients died of recurrence of rectal cancer. Disease-free survival rate at year 5 was 93.7%. Conclusions: Our study, one of the largest series in the world, confirms that TEM is a preferable option in the surgical treatment of T0 and T1a rectal carcinoma. As long as early cancer cases are treated, submucosal resection seems to be sufficient. When risk of recurrence is found by pathological examination, immediate salvage operation is mandatory to improve the prognosis.